Pendampingan dalam Penerapan Instrumen Penilaiaan Sikap Spiritual dan Sosial di MA Swasta Mamba’ul Hikam Putat Tanggulangin - Dhea Alfina Damatussolah; Hanim Afiyah (At- Ta'lim : Jurnal Pendidikan, 2021)
This paper examines the process of mentoring the application of an assessment instrument for spiritual and social attitudes at MA Mamba'ul Hikam Putat Tanggulangin. This was motivated by a problem in school that did not apply assessment instruments to students. This research was conducted with a period of 1 month in research and data processing with existing theories. The results of this study state that the self-assessment of students at MAS Mamba'ul Hikam can be used to foster values ​​of reconciliation and improve the ability to reflect or introspect, as follows: 1). Observation technique, 2). Self-assessment, 3). Assessment between friends and 4). Journal. b). Steps to make a description of the value / development of attitudes for one semester at MAS Mamba'ul Hikam. c). Assistance in the application of spiritual and social assessment instruments at MAS Mamba'ul Hikam was carried out with the observation stage, instrument development and implementation assistance carried out well.